Reconstruction of Sustainable Development through Education for Sustainable Development (ESD) to Strengthen National Resilience - A. Fatikhul Amin Abdullah; Agung Dwi Bahtiar El Rizaq; Muhammad Hadiatur Rahman; Sahrul Romadhon; Shinta Oktafiana; Faraniena Yunaeni Risdiana; Ahmad Imam Khairi; Itaanis Tianah; Siti Azizah (IAIN Madura, 2026)
Education for Sustainable Development (ESD) has become a strategic approach in supporting the achievement of the Sustainable Development Goals (SDGs) through the integration of environmental, social, cultural, policy, and technological transformation aspects within education. This study aims to analyze the trends of ESD research in Indonesia, Singapore and Japan based on several major themes, namely Culture and Social, Environmental and Energy, Policy and Regulation, and Technology and AI for Supporting ESD. The study employed a literature review approach by analyzing scientific articles from various national and international universities. The findings reveal that the implementation of ESD has evolved toward a multidisciplinary approach emphasizing the integration of local culture, ecological literacy, character education, educational policy, and digital transformation. Previous studies demonstrate that experience-based learning, inquiry learning, ethnopedagogy, and the utilization of Artificial Intelligence (AI) can enhance students’ critical thinking, creativity, digital literacy, social awareness, and environmental responsibility. Furthermore, the successful implementation of ESD is strongly influenced by the synergy among educational policies, local cultural values, technological innovation, and active community participation. Therefore, ESD should not merely be understood as environmental education, but rather as a process of social transformation that supports holistic and contextual sustainable development.